2002
DOI: 10.1038/nn956
|View full text |Cite
|
Sign up to set email alerts
|

Shared receptors in axon guidance: SAX-3/Robo signals via UNC-34/Enabled and a Netrin-independent UNC-40/DCC function

Abstract: The C. elegans SAX-3/Robo receptor acts in anterior-posterior, dorsal-ventral and midline guidance decisions. Here we show that SAX-3 signaling involves the C. elegans Enabled protein UNC-34 and an unexpected Netrin-independent function of the Netrin receptor UNC-40/DCC. Genetic interactions with gain- and loss-of-function mutations suggest that unc-34 and unc-40 act together with sax-3 in several guidance decisions, but the C. elegans Netrin gene unc-6 does not act in the same genetic pathways. Within the mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 49 publications
8
143
2
Order By: Relevance
“…Here, it should be noted that several clear examples of independent repulsive functions for Slit and Robo have been described in both C. elegans and Vertebrates (Brose and TessierLavigne, 2000;Zou et al, 2000;Stein and Tessier-Lavigne, 2001;Yu et al, 2002). Furthermore, studies in C. elegans have suggested that Slit repulsion and Netrin attraction act cooperatively during ventral guidance and that DCC/UNC-40 can actually potentiate SAX-3/Robo repulsion independently of Unc-6/Netrin (Hao et al, 2001;Yu et al, 2002).…”
Section: Independent Functions Of Netrin-fra and Slit-robo Regulate Mmentioning
confidence: 85%
“…Here, it should be noted that several clear examples of independent repulsive functions for Slit and Robo have been described in both C. elegans and Vertebrates (Brose and TessierLavigne, 2000;Zou et al, 2000;Stein and Tessier-Lavigne, 2001;Yu et al, 2002). Furthermore, studies in C. elegans have suggested that Slit repulsion and Netrin attraction act cooperatively during ventral guidance and that DCC/UNC-40 can actually potentiate SAX-3/Robo repulsion independently of Unc-6/Netrin (Hao et al, 2001;Yu et al, 2002).…”
Section: Independent Functions Of Netrin-fra and Slit-robo Regulate Mmentioning
confidence: 85%
“…Both signaling molecules act on conserved receptor systems, the activity of which is tightly regulated in a coordinated fashion (Stein and Tessier-Lavigne, 2001). Furthermore, both systems share downstream components, indicating that Netrin and Slit function is closely interwoven (Yu et al, 2002).…”
Section: Two Major Signaling Molecules Guide Commissural Growth Conesmentioning
confidence: 99%
“…In Drosophila robo mutants, too many axons cross and recross the midline (5). Several molecules have been implicated in the Robo signaling pathway, including the actin binding protein Enabled (6,7), the tyrosine kinase Abelson (Abl) (6,8,9), and the Ras͞Rho GEF Son of Sevenless (10,11). Nevertheless, our understanding of the signal-transduction mechanism leading from Slit͞Robo to cytoskeleton rearrangement during repulsive axon guidance remains incomplete.…”
mentioning
confidence: 99%